Effects of webGIS-based spatial intelligence training on Geography teacher's spatial skills - Lili Somantri; Siti Hamidah (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2023)
The inadequate spatial intelligence of teachers culminates in students’ minimum spatial intelligence. As teachers carry the role of learning facilitators and instruments, spatial intelligence training is highly substantial for geographic teachers. This study aims to identify the effects of spatial intelligence training based on webGIS on the geographic teachers’ spatial intelligence. This study used a quantitative method with a pre-experimental design and a one-group pretest-postest with paired sample T-test data analysis. Our analysis results using T-test showed Sig. (2-tailed) 0.00 less than 0.05, indicating the influence of spatial intelligence training based on webGIS on geography teachers’ spatial intelligence. Besides, the increase in teachers’ spatial intelligence is also shown by their increasing average test scores by 28.24 percent.